Diverse uncultivated bacterial groups from soils of the arid southwestern United States that are present in many geographic regions. - Kuske, C R (1997)
We have performed a phylogenetic survey of microbial species present in two soils from northern Arizona. Microbial DNA was purified directly from soil samples and subjected to PCR amplification with primers specific for bacterial 16S rRNA gene sequences (rDNAs). Clone libraries from the two soils were constructed, and 60 clone inserts were partially sequenced. Phylogenetic analysis of these sequences revealed extensive diversity. Most of the analyzed sequences (64%) fell into five novel clusters having no known cultured members. Extensive analysis of 10 nearly full-length rDNAs from clones representative of the novel groups indicated that four of the five groups probably cluster into a large "supergroup" which is as distinct from currently recognized bacterial divisions as the latter are from each other. From this we postulate the existence of a major bacterial lineage, previously known only from a single cultured representative, whose diversity and ecology we are only beginning to explore. Analysis of our data and that from other rDNA sequence-based studies of soils from different geographic regions shows considerable overlap of sequence types. Taken together, these groups encompass most of the novel rDNA sequences recovered in each comparable analysis reported to date, despite large differences in soil types and geographic sources. Our results indicate that members of these new groups comprise a phylogenetically diverse, geographically widespread, and perhaps numerically important component of the soil microbiota.